The “Technologically Assisted" Elderly: What are the Ethical Challenges? - Bier, Nathalie; Rialle, Vincent; Djellal, Abdelaziz; Jean, Miguel; Brissonneau, Christophe; Williams-Jones, Bryn (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2022)
In our increasingly digitalized society, do we really have a choice about whether or not to adopt technology? How does this digitalization impact the elderly in particular and their ecosystem? What are the ethical issues raised by this digitalization? This text aims to provide some food for thought in relation to these issues from the perspective of various experts in the fields of technology, aging and bioethics. These experts met during a symposium held in Angers, France, in October 2019. The text is a report of the exchanges and points of view of these experts, as well as of the open discussions they had with the audience, on the main issues raised by this digitalization from the perspective of the elderly, family caregivers, caregivers, society and research.